Algebras with genetic realization and corresponding evolutionary population dynamics - Ganikhodjaev, Nasir (American Mathematical Society, 2016)
In recent decades in game theory, evolutionary and dynamical aspects have increased in popularity. In this paper, we explore the nonassociative algebraic structure that naturally occurs in evolutionary population dynamics. We discuss a rock-paper-scissors game and describe the corresponding algebra.